Pengaruh Knowledge Dan Skill Terhadap Kinerja Melalui Kompetensi Kewirausahaan : Studi Pada Pengusaha UMKM Produk Unggulan Kab Pasuruan - Abdul Majid (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Micro, small enterprises (MSME) are businesses or industries that are supported by individual skills, creativity and abilities. Industry or business creates an item or product by utilizing a creativity and the talents of each individual. This study aims to determine the influence of Knowledge, Skills on business performance through entrepreneurial competence. This type of research is Quantitative research. The population in this study is the owner of MSME of Pasuruan Regency's superior products, the sample of this study is 1 16 Respondents The source of data in this study is the primary data source. Data collection techniques using questionnaires. The data analysis tool used is multiple linear regression analysis with the help of SPPS 22 Software. The results of this study show (1). Knowledge has a significant effect on business performance. (2). Knowledge has a significant effect on entrepreneurial competence (3). Skills have a significant effect on business performance. (4). Skills have a significant effecton entrepreneurial competence. (5). Entrepreneurial competence has a significant effect on performance. (6). Knowledge has a significant effect on business performance through the competence of the entrepreneur. (7). Skills have a significant effect on performance through entrepreneurial competence.